2015
DOI: 10.1111/1753-6405.12378
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B knowledge and associated factors among people with chronic hepatitis B

Abstract: Abstract:Objective: To assess hepatitis B knowledge among people with chronic hepatitis B (CHB) in Australia.Methods: People with CHB in three Australian jurisdictions completed a self-administered questionaire, including 24 hepatitis B knowledge questions across four domains: transmission; natural history; epidemiology and prevention; and clinical management.Results: Ninety-three people completed the survey. Mean age was 45 years, 43% were women and 93% were born overseas (75% from Asia). Mean total knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 26 publications
(47 reference statements)
8
39
3
1
Order By: Relevance
“…Insufficient knowledge or misconception about hepatitis B is one explanation for an unrealistic fear or reluctance to talk about hepatitis B with others. Previous studies have shown a positive association between academic education and knowledge of hepatitis B among people with CHB (14, 20, 24, 25) and a lower educational level can be a surrogate marker for less knowledge about hepatitis B. This hypothesis is supported by our findings indicating a higher proportion of participants with higher education were realistically worried about developing liver disease.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Insufficient knowledge or misconception about hepatitis B is one explanation for an unrealistic fear or reluctance to talk about hepatitis B with others. Previous studies have shown a positive association between academic education and knowledge of hepatitis B among people with CHB (14, 20, 24, 25) and a lower educational level can be a surrogate marker for less knowledge about hepatitis B. This hypothesis is supported by our findings indicating a higher proportion of participants with higher education were realistically worried about developing liver disease.…”
Section: Discussionsupporting
confidence: 86%
“…Changes in social behaviours, life style and the way they live due to a chronic disease are expected among patients living with a chronic disease. However, some additional negative attitudes among people with CHB coupled with misconceptions about hepatitis B transmission occurring through sharing foods, utensils, kissing and hugging (14, 20, 24, 25) may result in social isolation of people with CHB and consequently impair their social health. In a study from the United States, 43% of people with CHB reported dating less since they had been diagnosed with hepatitis B and 52% felt overwhelmed about dealing with hepatitis B (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of undertaking each withdrawal activity in the past month were collected with responses ranging from 0 (never) to 4 (very often). The total score ranged from 0 (never taken any of the preventative actions) to 20 (taken preventative actions very often for all of the activities).BBV transmission knowledgeParticipants rated 14 statements about HIV transmission [27], 31 about HCV transmission [28, 29] and 15 about HBV [30]. The total number of correct answers across each BBV transmission questionnaire was summed (range 0–14 for HIV, 0–31 for HCV and 0–15 for HBV).…”
Section: Methodsmentioning
confidence: 99%
“…Participants rated 14 statements about HIV transmission [27], 31 about HCV transmission [28, 29] and 15 about HBV [30]. The total number of correct answers across each BBV transmission questionnaire was summed (range 0–14 for HIV, 0–31 for HCV and 0–15 for HBV).…”
Section: Methodsmentioning
confidence: 99%